2018
DOI: 10.1111/jeb.13393
|View full text |Cite
|
Sign up to set email alerts
|

Niche differentiation among clones in asexual grass thrips

Abstract: Many asexual animal populations comprise a mixture of genetically different lineages, but to what degree this genetic diversity leads to ecological differences remains often unknown. Here, we test whether genetically different clonal lineages of Aptinothrips grass thrips differ in performance on a range of plants used as hosts in natural populations. We find a clear clone‐by‐plant species interactive effect on reproductive output, meaning that clonal lineages perform differently on different plant species and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 34 publications
(35 reference statements)
0
8
0
Order By: Relevance
“…The species-level generalist phenotype for A. rufus was due to a combination of very generalist clones (clone 4 and 8, Figure 2) and more specialized ones (clone 2 and 9). The latter perform best on different grass species ( Festuca rubra for clone 9 and Poa pratensis for clone 2; van der Kooi et al 2019), meaning they are characterized by different fundamental niches.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The species-level generalist phenotype for A. rufus was due to a combination of very generalist clones (clone 4 and 8, Figure 2) and more specialized ones (clone 2 and 9). The latter perform best on different grass species ( Festuca rubra for clone 9 and Poa pratensis for clone 2; van der Kooi et al 2019), meaning they are characterized by different fundamental niches.…”
Section: Resultsmentioning
confidence: 99%
“…We also found that the performance of asexual A. rufus females on Festuca rubra positively correlates with the abundance of this grass species at the location the females were collected (Figure 3). This, added to geographical niche variation, suggests that different grass communities favor different clonal assemblages, as different clones perform best on different grass species (van der Kooi et al 2019, Figure 2). Asexual Aptinothrips populations are also genetically highly diverse (van der Kooi and Schwander 2014; Fontcuberta García-Cuenca et al 2016), meaning that there is a large standing pool of ecologically divergent clones available for selection to act on.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…a "frozenniche" mechanism; Vrijenhoek 1979). Attempts to test these alternative predictions have mainly focused on study systems that are apomictic, hybrids (which are often also polyploid), or automictic parthenogens that reproduce via central fusion (Bierzychudek 1989;Oplaat and Verhoeven 2015;Van Der Kooi et al 2019;Hersh 2020). These reproductive pathways often lead to stable or even increased heterozygosity when compared to sexual relatives (Suomalainen et al 1987;Marescalchi and Scali 2003;Jaron et al 2021).…”
Section: Introductionmentioning
confidence: 99%